Rethinking Institutions and Organizations - Greenwood, Royston; Hinings, C. R.; Whetten, Dave (Journal of Management Studies, 2014)
AbstractIn this Point–Counterpoint article we argue that institutional scholarship has become overly concerned with explaining institutions and institutional processes, notably at the level of the organization field, rather than with using them to explain and understand organizations. Especially missing is an attempt to gain a coherent, holistic account of how organizations are structured and managed. We also argue that when institutional theory does give attention to organizations it inappropriately treats them as though they are the same, or at least as though any differences are irrelevant for purposes of theory. We propose a return to the study of organizations with an emphasis upon comparative analysis, and suggest the institutional logics perspective as an appropriate means for doing so.